Use of the automicrobic and enteric-tek systems for identification of Enterobacteriaceae. - Goldstein, J (1982)
Studies were performed to evaluate the use of the Enteric-Tek (ET) and the AutoMicrobic system (AMS) for the identification of 201 Enterobacteriaceae freshly isolated from clinical specimens. All test systems were inoculated simultaneously from the same MacConkey agar plate. Organisms were also identified with conventional media. Identifications with the ET and AMS agreed with those made with conventional biochemicals 97% of the time. At a 95% confidence level, the ET was able to identify 75% of the isolates within 18 h without the aid of additional biochemical tests; the AMS identified 92% in 8 h. Technologist time needed for identifications made with the AMS was reduced approximately 57% compared with the ET. In all instances in which the AMS identification disagreed with the conventional, the ET identified the organism correctly. Similarly, organisms misidentified by the ET were correctly identified by the AMS. The data suggest that the AMS and ET identify clinical isolates with comparable accuracy; however, the AMS offers a significant savings in time.